Needs analysis for the development of interactive multimedia-assisted contextual learning model based on elementary school student characteristics - Nurhizrah Gistituati; Rieke Alyusfitri; Yerizon (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The study analyzes considerations and directions in choosing the best learning model and media to help students understand the subject. They can complete it based on the characteristics of students so that students can be directly involved during the implementation of learning. A teacher must be able to apply a teaching method appropriate to his pupil's condition because characteristics are unique properties inherent in a person or an object. Each child has different learning characteristics and abilities, so to make learning enjoyable and engaging, it should be relevant to students' daily lives and supported by interactive multimedia. The research method employed was qualitative-descriptive. Meanwhile, the research data was collected through interviews and questionnaires with the students. Research was carried out at three elementary schools in Padang City with 60 subjects. Based on the study identified characteristics of students, among them, students enjoy playing (96.7%), enjoy working with groups (83.3%), engaged in learning activities using interactive multimedia (81.13%), and experienced direct involvement (80%) in the practice or use of such multimedia that arouses student interest in the learning material. Thus, based on the characteristics of elementary school students, contextual learning models aided by multimedia interactive support were implemented to help the learning process.